2020
DOI: 10.3389/fncel.2019.00591
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 Regulates Heat Acclimation-Induced Microglial M2 Polarization Involving the PI3K-Akt Pathway Following EMF Exposure

Abstract: The function of triggering receptor expressed on myeloid cells-2 (TREM2) has been described within microglia with a beneficial activated phenotype. However, the role of TREM2 underlying microglial phenotypic alterations in the cross-tolerance protection of heat acclimation (HA) against the inflammatory stimuli electromagnetic field (EMF) exposure is less well known. Here, we investigated the TREM2-related signaling mechanism induced by HA in EMF-stimulated N9 microglial cells (N9 cells). We found that EMF expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The Bcl-2 family of apoptotic proteins have been implicated in the Bcl-2 family Akt signaling response to amyloid. (Clementi et al 2006, Yin et al 2011, Shang et al 2012, Zhu et al 2015 However, even though TREM2related Akt signaling has been described (He et al 2019 to our knowledge a link between TREM2 specific signaling and Bcl-2 apoptosis has not been studied. Aβ42 treatment influences cell survival in HMC3 cells where after 8 hours there is a significant decline in viability (Fig4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bcl-2 family of apoptotic proteins have been implicated in the Bcl-2 family Akt signaling response to amyloid. (Clementi et al 2006, Yin et al 2011, Shang et al 2012, Zhu et al 2015 However, even though TREM2related Akt signaling has been described (He et al 2019 to our knowledge a link between TREM2 specific signaling and Bcl-2 apoptosis has not been studied. Aβ42 treatment influences cell survival in HMC3 cells where after 8 hours there is a significant decline in viability (Fig4).…”
Section: Discussionmentioning
confidence: 99%
“…(Shang et al 2012) The Bcl family of proteins have been implicated in the Bcl family Akt signaling response to amyloid. (Clementi et al 2006, Yin et al 2011, Zhu et al 2015 However, even though TREM2related Akt signaling has been described, (He et al 2019 to our knowledge a link between TREM2 specific signaling and Bcl-2 family mediated apoptosis has not been studied. In addition, TREM2 inhibits the inflammatory response to LPS in mouse microglia by suppressing the PI3K/NF-κB signaling, (Li et al 2019) but less is known about the response to Aβ in human microglia.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the M2 phenotype shows a ramified morphology by secreting neurotrophic and antinflammatory factors to maintain homeostasis of the CNS environment [ 6 ]. Suppression of the microglial M1 phenotype and promotion of the transformation to the M2 phenotype have been reported to ameliorate chronic neurological disorders, such as AD [ 7 ], Parkinson’s disease [ 5 ], stroke [ 8 ], LPS-induced neuroinflammation [ 9 ], and exposure to electromagnetic field-induced neuroinflammation [ 10 ]. Studies have shown that microglia are in a state of overactivation in diabetic cognitive decline attributed to disordered glucose metabolism [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…With technological development, electromagnetic radiation has gained increasing attention as a unique kind of pollution. Many studies on the biological effects of electromagnetic radiation have shown that electromagnetic radiation affects all systems of the body (1,2), including the central nervous system (CNS), gastrointestinal system, hematological system and reproductive system (3). The CNS is susceptible to electromagnetic pulse (EMP) radiation, which can cause learning and memory dysfunction (4).…”
Section: Introductionmentioning
confidence: 99%